2011
DOI: 10.1167/iovs.10-6255
|View full text |Cite
|
Sign up to set email alerts
|

What Reduction in Standard Automated Perimetry Variability Would Improve the Detection of Visual Field Progression?

Abstract: PURPOSE. The test-retest variability of standard automated perimetry (SAP) severely limits its ability to detect sensitivity decline. Numerous improvements in procedures have been proposed, but assessment of their benefits requires quantification of how much variability reduction results in meaningful benefit. This article determines how much reduction in SAP procedure variability is necessary to permit earlier detection of visual field deterioration. METHOD. Computer simulation and statistical analysis were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 20 publications
1
30
0
Order By: Relevance
“…44 At the same time, when perimetry with size III returns a defect of À5 dB at a visual field location on one visit, it may return a defect of À20 dB or 0 dB on the next visit. 3 The ability to reduce test-retest variability in defects has the potential 8 to make perimetry a more useful clinical tool in patients with severe damage, where imaging measures are no longer useful.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…44 At the same time, when perimetry with size III returns a defect of À5 dB at a visual field location on one visit, it may return a defect of À20 dB or 0 dB on the next visit. 3 The ability to reduce test-retest variability in defects has the potential 8 to make perimetry a more useful clinical tool in patients with severe damage, where imaging measures are no longer useful.…”
Section: Discussionmentioning
confidence: 99%
“…Increased variability also adds time and complexity to clinical trials that attempt to assess effects of treatment. [8][9][10] Increased test-retest variability is not present for frequency-doubling perimetry, which uses large, sinusoidal stimuli. [11][12][13][14][15] Knowledge about why frequency-doubling stimuli have this property could help identify a wider range of potential new stimuli for perimetry with improved test-retest variability near and within glaucomatous defects.…”
Section: Introductionmentioning
confidence: 99%
“…It remains to be seen whether this would reach the 20% reduction in variability that has been reported to be needed to reduce the average time taken to detect progression by one visit. 3 However, our study demonstrates the principle that reducing the technical range of perimetry would reduce variability not just in highly damaged regions of the visual field, but also in less damaged areas by allowing more precise thresholding within the same test duration.…”
Section: Discussionmentioning
confidence: 77%
“…However, results from perimetry are highly variable, especially in regions of more severe damage. 1,2 Simulation studies suggest that reducing variability (defined as the spread of the frequency-of-seeing [FOS] curve) by 20% would enable progression to be detected, on average, one visit sooner, 3 and more than that for many patients.…”
mentioning
confidence: 99%
“…Previous simulations have shown that this likely requires a reduction in variability of 20% to 40% at damaged locations. 24 Experiment Two demonstrated this magnitude of reduction only for observers making high rates of response errors. Smaller reductions in test-retest variability may still be beneficial, though, particularly in clinical trial situations where different approaches may be taken to progression detection, such as the ''wait and see'' approach recently suggested by Crabb and Garway-Heath.…”
Section: Discussionmentioning
confidence: 91%